Strombidium rassoulzadegani: A Model Species for Chloroplast Retention in Oligotrich Ciliates - McManus, George B.; Liu, Weiwei; Cole, Rachel A.; Biemesderfer, Daniel; Mydosh, Jennifer L. (Frontiers in Marine Science, 2018)
Strombidium rassoulzadegani is a planktonic ciliate that retains chloroplasts from its food and uses them to obtain a nutritional supplement from photosynthesis. Unlike most members of the Oligotrichida, it is not difficult to grow in culture and thus it can serve as an experimental model for this kind of mixotrophy. We report here on its distribution, seasonal pattern of occurrence in the western North Atlantic, and on experiments to elucidate patterns of encystment and excystment, preferred food algae, and heterotrophic growth. Among ten different microalgae, including members of the Dinophyceae, Chlorophyceae, Haptophyceae, Cryptophyceae, and Bacillariophyceae, only four could support growth for more than one week, and only the chlorophyte Tetraselmis chui (PLY 429) could consistently support sustained growth in the dark. Of the four algae that supported growth, three also resulted in longer survival when the ciliate was subsequently starved in the light, compared to the dark, suggesting that all of them provided some photosynthetic benefit to the ciliate. The dinoflagellate Prorocentrum minimum (JA) supported similar survival in the light and dark and likely does not undergo chloroplast retention in the ciliate.